Trans-cending time: lived experiences and well-being of older Filipino transgenders - Sagarbarria, Maria Celeste Borja; Ignacio, Maita Doliente (UIN Maulana Malik Ibrahim Malang, 2024)
This study, utilizing Interpretative Phenomenological Analysis (IPA), delves into the experiences of three Filipino transgenders in their 50s, focusing on how they perceive aging and its effects on well-being. The findings reveal a mix of negative encounters, such as prejudice and financial difficulties, alongside positive experiences, including supportive relationships and community involvement. Participants emphasize the importance of helping others and assert that being transgender is an integral aspect of their humanity. They advocate for transgender empowerment based on their learned experiences, viewing aging as a period necessitating financial, physical, and relational preparations, while also embracing growth. Aging is seen as conducive to happiness and gratitude. The study discusses implications for both individual and societal levels, including family dynamics, legal rights, and the need for safe spaces. Recommendations for community action and further research are provided. KEY WORDS: filipino transgenders; aging; well-bein; lived experiences